CEO Turnover and Firm Performance In Indonesia - Setiawan, Doddy; Phua, Lian Kee; Chee, Hong Kok; Trinugroho, Irwan (The Indonesian Capital Market Review, 2017)
We investigated the effect of changes in CEO position on subsequent firm performance by studying 91 CEO turnovers in Indonesia. Our results show that firm performance decreases during the turnover year. Moreover, the incoming CEO does not increase firm performance in subsequent years. Indeed, there is evidence that firm performance decreases after such turnovers. We ultimately conclude that CEO turnovers in Indonesia do not have a positive effect on firm performance. Going further, we divided CEO turnovers into routine and non-routine turnovers on the basis of the turnover process. Both routine and non-routine CEO turnovers show similar results with all samples, in which the incoming CEO in a routine or non-routine turnover does not have a positive effect upon firm performance. Further evidence suggests that the incoming CEO tends to upsize firm assets rather than downsize them.